2006
DOI: 10.1183/09031936.06.00087705
|View full text |Cite
|
Sign up to set email alerts
|

Continuous positive airway pressure treatment for sleep apnoea: compliance increases with time in continuing users

Abstract: Continuous positive airway pressure (CPAP) remains the best treatment for sleep apnoea syndrome (SAS). In the 1990s, many authors reported on daily compliance, but all of the studies utilised relatively short periods of follow-up that did not exceed a few years.The mean annual rate of CPAP use in patients with SAS was prospectively recorded. In the current study, the results are presented along with compliance data from patients who started CPAP between 1991 and 1998 and were still using it by the end of 2003.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 13 publications
3
29
1
1
Order By: Relevance
“…As CPAP is a chronic treatment and, in most cases, must be used for life, good compliance is essential to achieve the beneficial effects of this therapy [8]. Although adherence to CPAP treatment has been extensively investigated in the literature [9][10][11][12][13][14][15][16][17][18][19][20], females have scarcely been represented in these series and no study to date has been specifically devoted to them. We therefore do not know how good adherence is in this population, and which variables can predict long-term compliance.…”
Section: Introductionmentioning
confidence: 99%
“…As CPAP is a chronic treatment and, in most cases, must be used for life, good compliance is essential to achieve the beneficial effects of this therapy [8]. Although adherence to CPAP treatment has been extensively investigated in the literature [9][10][11][12][13][14][15][16][17][18][19][20], females have scarcely been represented in these series and no study to date has been specifically devoted to them. We therefore do not know how good adherence is in this population, and which variables can predict long-term compliance.…”
Section: Introductionmentioning
confidence: 99%
“…KRIBBS et al [14] found an utilisation rate of 66% of the days monitored. A recent study by SUCENA et al [13] showed an increase in compliance in continuing users in the long term with 5.35 h after 1 yr and 6.55 h after 10 yrs. 23% of patients quit CPAP within 5 yrs, most of them during the first year.…”
Section: Discussionmentioning
confidence: 99%
“…The use/ comfort of CPAP therapy may be limited by side effects, such as mucosal irritation, mask dislodgement, mask leak or difficulty in exhaling, which may critically impair compliance [7][8][9][10][11][12] or lead to discontinuation of therapy; 23% of patients quit CPAP within 5 yrs, most of them during the first year [13]. In other publications, discontinuation rates ranged from 8 [11] to 46% [14].…”
mentioning
confidence: 99%
“…Many studies have statistically evaluated compliance over relatively brief periods of time (one to six months) [16] [17] [18]. Long-term studies are far fewer and rare to find [19] [20]. In these reports, the reasons for noncompliance have often been inadequately documented.…”
Section: Introductionmentioning
confidence: 99%